Discovering statistics using IBM SPSS statistics - Field, Andy P. (SAGE Publications, 2018)
Unrivalled in the way it makes the teaching of statistics through the use of IBM SPSS statistics compelling and accessible to even the most anxious of students. The only statistics textbook you and your students will ever need just got better!